Pengaruh Pemanfaatan Teknologi Aplikasi Carik Jakarta dan Partisipasi Masyarakat Terhadap Efisiensi Pendataan Keluarga di Kelurahan Kampung Melayu Kecamatan Jatinegara Jakarta Timur - Achmad Khizam Fikri Aditama; Adin Dahuri (Jurnal Ilmu Administrasi Publik, 2025)
Family data collection is one of the important elements in social development planning, health, and public services. Therefore, this research aims to determine the influence of the Utilization of the Carik Jakarta Application and Community Participation on Data Collection Efficiency in Kampung Melayu Village. This research uses a quantitative method with a questionnaire data collection technique distributed to 67 respondents. The results of the research shows a positive influence between the utilization of the Carik application and community participation on data collection efficiency of 5.6% and 86.2%, respectively. while the F test shows that the two variabels simultaneous have a significant effect on data collection efficiency (sig. 0.000 <0.05) F count 90.838 F table 3.14. the coefficient of determination (R Square) of 0.598 indicates that 73.1% of data collection efficiency is influenced by these two variables, while 26.9% is influenced by other factors. Keywords Utilization, Carik, Participation, Efficiency, Data Collection